Semantic decomposition of four Quranic words - Mark Durie (Russian Journal of Linguistics, 2022)
In this paper, the author proposes Natural Semantic Metalanguage (NSM) semantic decompositions of four difficult-to-translate quranic Arabic words using Natural Semantic Metalanguage (Goddard Wierzbicka 2014, Wierzbicka 2021). This is the first study to propose an explicit semantic explication of these core Islamic lexical items, which are foundational for the spiritual worldview of the almost two billion followers of Islam in the world today. The first word considered is rasūl , which refers to intermediaries sent by Allah to humans and is used in the Quran alongside nabī , which has almost the same meaning. An NSM semantic explication of rasūl is contrasted with explications of biblical Hebrew nābā’ ‘prophesy’ and nabī’ ‘prophet’. In English translations of the Quran, rasūl is usually rendered as ‘messenger’ and nabī as ‘prophet’, yet these translations are misleadingly inadequate. Three further quranic concepts are examined, which have received the most diverse and unsatisfactory renderings in English translations of the Quran: shirk ‘association’ and kāfir ‘disbeliever’ refer to two dimensions of disbelief, and ittaqā , a difficult-to-translate verb, refers to cautious piety. The use of Natural Semantic Metalanguage overcomes the resistance of these terms to translation into English, by means of fine-grained semantic explications using semantic primes. These explications are designed to be readily accessible to speakers of languages other than English.